Of pilgrimages and restorations: religion, heritage and politics in divided Cyprus - Mesaritou, Evgenia (Politics and religion, 2024)
This paper explores the intersections of religion, heritage, and politics in divided societies by focusing on two events that occurred in Cyprus before the crossing points opened (2003). These are the Greek and Turkish Cypriot reciprocal pilgrimages to a Christian and Muslim site, respectively, and the two sites' restoration. I argue that in these events the Cyprus Issue effected the transformation of pilgrimage practices and sites into matters of political agreement, implicating them in processes of conflict management and resolution. In this context, pilgrimage facilitated inter-communal exchanges and intra-communal frictions and antagonisms that question binary oppositions through which questions of conflict and amity have been debated in pilgrimage studies.